Optimization of a wind farm by coupled actuator disk and mesoscale models to mitigate neighboring wind farm wake interference from repowering perspective. (15th September 2021) - Khan, Mehtab Ahmad; Javed, Adeel; Shakir, Sehar; Syed, Abdul Haseeb
Highlights: Inter-farm wake losses intensify due to uncoordinated wind farm development. Repowering augments the power generation capacity of existing wind farms. Coupled mesoscale and microscale simulations provide a swift repowering analysis. Power is increased by vertical and horizontal relocation of wake affected turbines. Abstract: This study explores the effects of inter-farm wakes and proposes staggering schemes that are most suitable for optimization of existing wind farm arrays to mitigate the effects of compound wakes. The case study considers a total of 9 out of 33 most deteriorated wind turbine for a microscale numerical analysis using the steady-state actuator disk model coupled with the mesoscale boundary condition data. Furthermore, the convective atmospheric boundary layer has also been considered. For vertically staggered layouts, the effect of the inter-farm wakes appeared mild at 100 m, modest at 80 m, and high at 60 m; as the maximum velocity deficit observed under the influence of compound wakes is approximately 13.3%, 14.1%, and 15.2%, respectively. Onsite recorded power data has been used to validate the baseline predicted powers at 80 m hub height. Both vertical and horizontal staggering options have been assessed for partial repowering. By elevating the turbines to a 100 m hub height, the cumulative power generation from the 9 × turbines increased by approximately 13.5% while reducing the hub height to 60 m decreased the power output by approximately 11.5% of that of the baseline at 80 m hub height. Further increase in cumulative power of up to 23% compared to existing layout is achieved by applying a lateral repositioning of 3 × underperforming turbines now positioned at 100 m hub height. This paper hence presents an applied insight for partial repowering of onshore wind farms affected by inter-farm wakes.